2018
DOI: 10.4066/biomedicalresearch.29-18-1091
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal haemorrhage in the new born: revisited

Abstract: Background: Adrenal haemorrhage (AH) in the new-born is not that uncommon and has been reported frequently. AH occurs most often after a traumatic delivery or complicated neonatal course. Design and setting: A retrospective, hospital-based study conducted at king Khalid university hospital (KKUH), endocrine service, Riyadh, Saudi Arabia, during the period January 2014 and July 2018. Methods: Medical records of neonates who had been diagnosed to have AH were reviewed. Data included age, sex, clinical manifestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Neonatal adrenal hemorrhage (NAH) is most common in term babies born vaginally and mostly affects males. 1,7 In this study, NAH was observed more frequently in term babies born vaginally, in line with the literature. On the contrary, our female cases were more common with a rate of 57%.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Neonatal adrenal hemorrhage (NAH) is most common in term babies born vaginally and mostly affects males. 1,7 In this study, NAH was observed more frequently in term babies born vaginally, in line with the literature. On the contrary, our female cases were more common with a rate of 57%.…”
Section: Discussionsupporting
confidence: 91%
“…Jaundice, signs of ischemia, palpable abdominal mass and anemia may be detected. 1,7,10,11 by the breakdown of red blood cells, is the most common presentation. 7 Adrenal insufficiency rarely occurs, usually in the first postnatal week.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations